Peran Organisasi dan Suasana Inovasi untuk Kinerja UKM - Luis Andrew Abraham; Jani Rahardjo (Jurnal Titra, 2015)
Lately the number of small and medium industry in Indonesian increase sharply, even though this growth was not followed by the development of internal organization and the innovation environment. While the development of internal organization and innovation may improve the performance of the small and medium industry. This research aims to model the increase in performance of shoes industries at Mojokerto thorugh the innovation atmosphere which can be influenced by internal organization as well. We used Structural Equation Modelling (SEM) to model the three variables (Interanal Organization, Innovation Atmosphere, and Performance) and developed questionnaire for the latent variables. We found that the internal organization which supported by the atmosphere of innovation did not significantly influence the industry performance.